Hubungan Daya Ledak Otot Tungkai dengan Kemampuan Shooting Pemain Sepak Bola U17 Persatuan Sepak Bola Rambatan - Farhan, Muhammad; Putra, Aldo Naza (Lembaga Yasin AlSys, 2025)
This study is motivated by the crucial role of lower limb explosive power in supporting the shooting performance of football players, alongside the limited research specifically linking these two variables in adolescent groups. The objective of this research is to examine the relationship between lower limb explosive power and shooting ability in 17-year-old football players at Persatuan Sepakbola Rambatan. A quantitative approach with a correlational design was employed. The sample consisted of 40 players selected through total sampling from the entire population. Measurement instruments included the standing broad jump test to assess lower limb explosive power and a goal-shooting test from three different angles with six attempts to evaluate shooting ability. Data were collected through direct observation and documentation, and analyzed using the Liliefors normality test and Pearson Product Moment correlation test. The results indicate a significant relationship between lower limb explosive power and shooting ability, with a calculated t-value of 2.18 exceeding the critical t-value of 1.68, indicating a positive and significant contribution. These findings confirm that explosive strength of the lower limbs is a key factor that should be developed to enhance shooting ability in youth football players. The study provides practical implications for coaches in designing physical training programs that emphasize lower limb strengthening to support players’ technical performance.